The concept of «suggestion» in the scientific research of the past and present (Pedagogy of Higher and Secondary Education, 2013)
Mischanchuk V. N. The concept of «suggestion» in the scientific research of the past and present.The article considers the concept «suggestion», examines the role of conscious and unconscious mechanisms of suggestion, reveals the experience of suggestive technologies use in teachers of music professional training.
Keywords: suggestion; conscious; unconscious; suggestologiya; future teacher of music